2017
DOI: 10.1177/2158244016677325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Consumers’ Self-Image and Demographics on Preference for Healthy Labeled Foods

Abstract: Consumers are becoming more health conscious. Increasingly, products that are labeled "healthy" are being marketed as new retailers and new brands vie for the consumers' share of wallet. This research identifies the self-image factors that constitute a health conscious image of the self and examines how self-image impacts consumer buying of foods that are labeled healthy. It also makes an effort to find out whether specific self-image factors are significantly associated with demographics. This study employs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 125 publications
(153 reference statements)
0
6
0
Order By: Relevance
“…Data show that a great proportion of Spanish population links health and sustainability. Research has demonstrated the health consciousness influences on purchasing habits [ 91 , 92 ]. Health consciousness can result in a deeper interest in knowing the characteristics of a sustainable diet, as well as linking sustainability to health can improve the shift to a more environmentally friendly food purchasing.…”
Section: Discussionmentioning
confidence: 99%
“…Data show that a great proportion of Spanish population links health and sustainability. Research has demonstrated the health consciousness influences on purchasing habits [ 91 , 92 ]. Health consciousness can result in a deeper interest in knowing the characteristics of a sustainable diet, as well as linking sustainability to health can improve the shift to a more environmentally friendly food purchasing.…”
Section: Discussionmentioning
confidence: 99%
“…Another gap in the literature for consumer preference of online fresh food shopping is that most existing studies are based on stated preference using survey data [16,17], or using home scan data [9] without any store attributes. Further, there exist many studies on consumers' willingness-to-pay (WTP) for food attribute labels that are of healthy food, food-safety and eco-relevance such as green food and organic food certificates [18][19][20][21][22][23]. However, their survey-based methods in eliciting these WTPs may have hypothetical bias, a severe disadvantage over revealed preference using actual sales data [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In the food choice variable, the selfconsciousness and emotional intelligence were positively related to food choice and toward the value of healthy food due to the preference in choosing healthy food (Hanspal & Devasagayam, 2017). However, the life stage was not related to food choice and toward value for healthy food because of the sociodemographic characteristic diff erences (Konttinen et al, 2021), life transitions (Winpenny et al, 2018), and external impact (Chen & Antonelli, 2020).…”
Section: Psychological Determinants Toward the Value Of Healthy Foodmentioning
confidence: 99%